Perlindungan Hukum Anak dalam Perwalian Terkait Peralihan Harta Peninggalan Orang Tua Kepada Wali Menurut Hukum Perdata - Alwi Bin Syeh Abubakar; Felicitas Sri Marniati; M. Slamet Turhamun (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Guardianship has an important role in supervising minors, including the management of their parents' inherited property as stipulated in Article 51 paragraph (3) of the Marriage Law. However, the practice shows that there is an abuse of authority by the guardian, who controls and even transfers inheritance not for the benefit of the child. This research aims to examine the legal consequences of the transfer of the inheritance of minors to guardians as well as the forms of legal protection available, with a case study of the Banten High Court Decision Number 89/Pdt/2015/PT BTN. The method used is normative legal research with legislative, conceptual, analytical, and case approaches, and uses legal consequences theory from R. Soeroso and legal protection theory from Satjipto Rahardjo. The results of the study show that the control of property by the guardian can cause the loss or escape of the child's inheritance, especially if there is no strict supervision and regulation. Therefore, it is necessary to affirm the legal status of children's inheritances, regulate the authority of guardians more strictly, and apply effective legal sanctions to prevent abuse. The litigation route is an important instrument in legal protection so that children can regain their rights fairly. This research contributes to strengthening the guardianship legal system in Indonesia, especially in the context of protecting children's rights to inheritance.